Fomos engolidos pelos dados?: a datificação na educação matemática. - Paladini, João Velasques (Universidade do Vale do Rio dos Sinos, 2025)
This doctoral research investigates how datafication impacts mathematics teaching in the context of Brazilian basic education. The central research question is: How does the process of datafication contribute to problematizing mathematics teaching in the context of teachers who teach mathematics? To answer this question, the study is based on the Cartographic Research-Intervention Method, tracking the trajectories of teacher-researchers in a datafied educational environment. The cartographic literature review allowed for mapping conceptions of datafication in education, its implications, and challenges. It was identified that datafication is not merely a process of data collection but constitutes a new learning ecology, reconfiguring the relationship between teachers, students, and knowledge. The study problematizes the appropriation of digital technologies in mathematics teaching, analyzing how pedagogical practices are influenced by big data, algorithms, and digital platforms. The results indicate that a naive understanding of datafication can reinforce inequalities and reductionist educational practices, while critical and ecological approaches enable the reinvention of methodologies, enhancing mathematics teaching and learning in a hybrid and connected environment.
Keywords: Educação matemática; Datificação; Educação digital; Ecologias conectivas; Pesquisa-intervenção; Mathematics education; Datafication; Digital education; Connective ecologies; Research-intervention; ACCNPQ::Ciências Humanas::Educação